2013
DOI: 10.1177/1534735413490233
|View full text |Cite
|
Sign up to set email alerts
|

Rasayana Drugs From the Ayurvedic System of Medicine as Possible Radioprotective Agents in Cancer Treatment

Abstract: The use of ionizing radiation, which is the cornerstone of cancer treatment, is compromised by the radiosensitivity of normal tissues. A chemical that can give selective benefit to the normal cells against the deleterious effects of ionizing radiation has been a long-sought goal. However, most of the compounds studied have shown inadequate clinical application owing to their inherent toxicity, undesirable side effects, and high cost. Studies carried out in the past 2 decades have shown that some of the classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
(101 reference statements)
0
19
0
Order By: Relevance
“…Studies have concluded that Triphala may help prevent and reverse DNA damage and mutagenesis. 53 The prevention of DNA damage is important given that it is often an initiating event in carcinogenesis. Research in animal models and in vitro has shown that Triphala is effective in prevention of mutagenesis induced by both chemical- and radiation-induced damage.…”
Section: Therapeutic Uses and Studiesmentioning
confidence: 99%
“…Studies have concluded that Triphala may help prevent and reverse DNA damage and mutagenesis. 53 The prevention of DNA damage is important given that it is often an initiating event in carcinogenesis. Research in animal models and in vitro has shown that Triphala is effective in prevention of mutagenesis induced by both chemical- and radiation-induced damage.…”
Section: Therapeutic Uses and Studiesmentioning
confidence: 99%
“…Triphala (Sanskrit; Tri = three and Phala = fruits) is defined as a well known tri-herbal Indian Ayurvedic formulation consisting of dried fruits of the three plant species, Emblica officinalis (Amalaki or the Indian Gooseberry) (Family-Euphorbiaceae), Terminalia bellirica (Bibhitaki or Karitaki) (Family-Combretaceae), and Terminalia chebula (Haritaki) (Family-Combretaceae) that are native to the Indian subcontinent (Ozah, 2020;Saxena et al, 2017;Dhanalakshmi et al, 2007;Mukherjee et al, 2006;Baliga et al, 2012Baliga et al, , 2013Baliga, 2010;Peterson et al, 2017;Malabadi et al, 2021a;Rasool and Sabina, 2007;Kumari et al, 2009;Ozah, 2020). In India, this triherbal combination of dried fruits, Triphala is very famous and used as a traditional home remedy for combating common cold, throat infections, antimicrobial, antiviral, antibacterial and antifungal infections (Malabadi et al, 2021a;Shanbag, 2015;Pradeep et al, 2016;Peterson et al, 2017;Mamgain et al, 2016;Bhattacharjee et al, 2015).…”
Section: Triphala: An Indian Ayurvedic Formulationmentioning
confidence: 99%
“…The other potential medicinal uses of Triphala, which include free radical scavenging, antioxidant, antifungal, antibacterial, antiviral, hypolipidemic effects, antimicrobial, antiallergic, anti-inflammatory, immunomodulating, appetite stimulation, gastric hyperacidity reduction, dental caries prevention, antipyretic, analgesic, antimutagenic, wound healing, anticariogenic, antistress, adaptogenic, hypoglycemic, anticancer, hepatoprotective, chemoprotective, radioprotective, and chemopreventive effects (Baliga et al, 2012;Zhang et al, 2021;Phetkate et al, 2012;Naik et al, 2005;Jagetia et al, 2002Jagetia et al, , 2004Reddy et al, 2009;Gautam et al, 2012;Biradar et al, 2007Biradar et al, , 2008Peterson et al, 2017;Belapurkar et al, 2014;Nariya et al, 2009;Rayudu and Raju, 2014;Dhanalakshmi et al, 2007;Kalaiselvan and Rasool, 2016;Mukherjee et al, 2006;Rasool and Sabina, 2007;Kumari et al, 2009;Saxena et al, 2017). Triphala has been reported as a potential antineoplastic agent and Triphala exerts an antineoplastic effect on many cancer cell lines, including those of the breast, prostate, colon, and pancreas (Baliga, 2010(Baliga, , 2013Kaur et al, 2005;Peterson et al, 2017;Vadde et al, 2015;Sandhya et al, 2006;Deshpande et al, 2014). Therefore, Triphala could be used as a potential adjunct therapy in the management of colon and other cancers.…”
Section: Triphala: Pharmacologymentioning
confidence: 99%
“…Many preclinical and clinical studies are ongoing with the radioprotective effects of plants. Studies reported that the ayurvedic formulations such as Triphala, Amritaprasham, Chyavanprasha, Ashwagandha Rasayana, Brahma Rasayana, and Narasimha Rasayana are effective radioprotectors by means of scavenging free radicals, decreasing oxidative stress, inhibiting DNA damage, and regenerating bone marrow progenitors, anti-inflammatory chemoprotection, and immunomodulatory mechanisms (Baliga, Meera, Vaishnav, Rao, & Palatty, 2013).…”
Section: Fortification Of Risks Of Radiotherapymentioning
confidence: 99%